RESEARCH PUBLICATIONS OF PHYSICS AT THE INDIAN INSTITUTE OF SCIENCE, BENGALURU: A SCIENTOMETRICS STUDY - D, Ramanjaneyareddy; K, Purnasekhar.; A, Pavani.; C, Lakshmi. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The study attempts to analyse research publications of the Indian Institute of Science, Bengaluru in physics during the period 2010 - 2019. The bibliographic data for this study was extracted from the Web of Science (WoS) Core Collection database. The study analyses the year-wise research publications, types of document, preferred journals for publication, prolific author, h-index, most collaborating institutions and countries, etc. This paper analyses 2593 research papers published by scientists of the Department of Physics, Indian Institute of Science, Bengaluru during the period under the study. The findings indicate that the growth of literature pattern is linear, and journals articles (2421) are the most preferred form of publications by the researchers to communicate their research. Ajay Kumar Sood is found to be the most prolific author and Physical Review B is the most preferred journal. In the most cited publications, only one paper was single-authored and other 19 research papers were multiple-authored. Indian Institute of Technology and Jawaharlal Nehru Centre for Advanced Scientific Research were the leading collaborating institutions (195). The USA, Germany, France, England, and Sweden were the top five most collaborative countries.